The Development of Human Capital within the Framework of the Demographic Economy of Ukraine: Factors of Stability - Bilorusets, Lesia; Mylenkyi, Vladyslav; Lunova, Tetiana; Zhurba, Oleksandr; Samoilenko, Viktoriia (International Journal of Economics and Financial Issues, 2025)
This study investigates the role of demographic, economic and social factors in shaping labor force participation and sustaining human capital in demographic economy of Ukraine. Current work focuses on demographic indicators such as birth rate, net migration and literacy rate and also considers economic indicators like education spending, unemployment and labor productivity, to identify critical drivers of workforce engagement. Using regression analysis (2000 to 2023) and SWOT evaluation, the findings reveal that while demographic decline and negative migration trends negatively impact labor force participation, higher investment in education, improved literacy rates, and enhanced labor productivity significantly contribute to workforce engagement and economic integration and growth. SWOT analysis identifies high literacy rates, skilled labor, and EU integration as key strengths and opportunities that enhance workforce engagement, drive innovation, and facilitate integration into global markets. And weaknesses identified are low birth rates and underfunded education, along with threats such as brain drain and political instability, challenge sustainable human capital development. Policy recommendations are provided to address these challenges and foster a productive labor market for long-term growth, social mobility and innovative development.